2017
DOI: 10.1186/s12879-017-2711-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lower extremity wound infection due to Kerstersia gyiorum in a patient with Buerger’s disease: a case report

Abstract: Background Kerstersia gyiorum is an extremely rare pathogen of human infection. It can cause chronic infection in patients with underlying conditions. It can easily be misdiagnosed if proper diagnostic methods are not used.Case presentationA 47-year-old male patient with a history of Buerger’s Disease for 28 years presented to our hospital with an infected chronic wound on foot. The wound was debrided, and the specimen was sent to Microbiology laboratory. Gram staining of the specimen showed abundant polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Clinical reports showed that some of K . gyiorum isolates were resistant to ciprofloxacin [2, 8], colistin [10], cefepime and ceftazidime [7], which suggested potential drug resistance genes or efflux pumps. K .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical reports showed that some of K . gyiorum isolates were resistant to ciprofloxacin [2, 8], colistin [10], cefepime and ceftazidime [7], which suggested potential drug resistance genes or efflux pumps. K .…”
Section: Resultsmentioning
confidence: 99%
“…gyiorum [2, 3, 513]. Among them, seven cases were associated with chronic otitis media [2, 5, 6, 8, 11, 13], three with chronic leg wound [2, 7, 10]. Additionally, K .…”
Section: Introductionmentioning
confidence: 99%
“…Kerstersia gyiorum is a pathogen that is infrequently reported in humans [ 1 ]. This bacterium, first classified in 2003, is a gram-negative coccobacillus belonging to the family Alcaligenaceae , which is isolated from water, soil, animal, and human specimens [ 2 3 ].…”
mentioning
confidence: 99%
“…The species was identified as K. gyiorum by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) with a MALDI Biotyper using MALDI-Biotyper software (version 2.3, Bruker Daltonics, Bremen, Germany). 16S ribosomal RNA gene sequencing was performed using primers 27F (5′-AGAGTTTGATCCTGGCTCAG-3′) and 1492R (5′-GGTTACCTTGTTACGACTT-3′) as described previously [ 1 ]. We obtained a consensus sequence of 1,394 bp, which was 99.9% identical to K. gyiorum LMG 5906 (GenBank accession number AY131213).…”
mentioning
confidence: 99%
See 1 more Smart Citation